Encyclopedia of condensed matter physics - Chakraborty, T. (Tapash), 1950- (Academic Press, 2024)
Encyclopedia of Condensed Matter Physics, Second Edition, Five Volume Set is an authoritative and comprehensive expansion of the classic 2005 work, delivering over 300 brand new or fully updated articles focused on core theoretical discoveries and modern applications. Meticulously planned and structured into approximately 60 sections, the book allows the user to quickly gain a solid footing in the key theoretical aspects of quantum mechanics, mechanics, electrodynamics, relativity, statistical mechanics and the elementary particles that form the core physics background for the field. The work also presents useful coverage of experimental techniques, materials processing, and materials systems, as well as applied topics. Novel topics, including topology in condensed matter, graphene, integer and fractional quantum Hall effect, and other nanoscale phenomena in optics, in semiconductors, and in superconductors are presented in unusual depth. The encyclopedia solves the problem that students and interdisciplinary researchers often have of finding clear, accessible foundational information to answer their initial questions on a topic.